The Effect Of Compensation and Organizational Climate onEmployee Job Satisfaction Moderated by Organization Commitment at BPJS Ketenagakerjaan Aceh - Maqhfirrah Atriana; Mesra B (CV. Doki Course and Training, 2026)
This study aims to analyze the effect of compensation and organizational climate on job satisfaction at BPJS Ketenagakerjaan Aceh with organizational commitment as a moderating variable. The sample of this study consisted of 100 employees selected using a purposive sampling method. Data were collected through questionnaires and analyzed using the Partial Least Square (PLS) method. The results of the study indicate that: (1) compensation has a positive and significant effect on job satisfaction, (2) organizational climate has a positive and significant effect on job satisfaction, and (3) organizational commitment as a moderating variable does not have a significant effect on the relationship between compensation and organizational climate with job satisfaction. This study concludes that job satisfaction of at BPJS Ketenagakerjaan Aceh employees can be further improved through improving the compensation system and strengthening the organizational climate, while the role of organizational commitment as a moderator needs to be studied further.